The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/met7120518
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Boron Nitride Impregnated Silane Composite Coating for Corrosion Resistance of Magnesium Alloys for Temporary Bioimplant Applications

Abstract: Magnesium and its alloys are attractive potential materials for construction of biodegradable temporary implant devices. However, their rapid degradation in human body fluid before the desired service life is reached necessitate the application of suitable coatings. To this end, WZ21 magnesium alloy surface was modified by hexagonal boron nitride (hBN)-impregnated silane coating. The coating was chemically characterised by Raman spectroscopy. Potentiodynamic polarisation and electrochemical impedance spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In order to improve the mechanical properties of biomaterials and increase their biocompatibility, h-BN has been used in many studies as a biocomposite component [8,9,36,[48][49][50]59,60]. For example, in one study, it was demonstrated that some particular mechanical properties of HA were improved with the addition of boron nitride nanotubes, and it was reported that there was no negative effect on the viability and proliferation of osteoblast cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the mechanical properties of biomaterials and increase their biocompatibility, h-BN has been used in many studies as a biocomposite component [8,9,36,[48][49][50]59,60]. For example, in one study, it was demonstrated that some particular mechanical properties of HA were improved with the addition of boron nitride nanotubes, and it was reported that there was no negative effect on the viability and proliferation of osteoblast cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, corrosion produces metal debris or soluble metallic ions, which creates long-term detrimental effects on the human body such as metallosis, toxic, or allergic reactions [38][39][40]. It should be noted that this type of coating has to be compatible with the human body, for which inert 2D coatings (i.e., graphene and hBN) are suitable candidates [38,41]. For example, graphene coatings exhibited a reduced corrosion rate of Cu metal in several biological solutions such as fetal bovine serum (FBS), Hank's balanced salt solution (HBSS), phosphate buffered saline (PBS), and cell culture media [38].…”
Section: Biomedicalmentioning
confidence: 99%
“…However, Mg is a bioresorbable metal that has properties similar to human bones that can be used as a replacement [42]. Through conjugation with biocompatible 2D material coatings (e.g., hBN-silane 2D composite), the precise resorption rate of Mg can be engineered to time the Mg temporary implant service life [41].…”
Section: Biomedicalmentioning
confidence: 99%
See 1 more Smart Citation
“…But their unacceptably rapid corrosion in human body fluid requires a coating that provides the required corrosion resistance, while also being biocompatible. To this end, the first study included in this special issue investigated the hexagonal boron nitride (hBN)-impregnated silane coating for an advanced magnesium alloy (WZ21) for bioimplant applications [1]. This coating was found to provide a five-fold improvement in the corrosion resistance in human body fluid.…”
mentioning
confidence: 99%